STRATEGI PEMERINTAH DAERAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH DI TENGAH PANDEMI COVID-19 - GEE, HARIANI; PANJAITAN, RAYA; PANJAITAN, FERRY (LP2MTBM MAKARIOZ, 2021)
The emergence of the Covid-19 pandemic which resulted in disruption of the community's economy which affected the increase in the Regional Original Income of Kabupaten Nias Selatan, of course the Regional Government of Kabupaten Nias Selatan has a strategy in increasing PAD. This study aims to determine the strategy Regional Government Kabupaten Nias Selatan in increasing Regional Original Income during the Covid-19 pandemic. This type of research is qualitative research. Data collection techniques by means of in-depth interviews, documentation. The data analysis technique used in this research is inductive analysis techniques, namely data reduction, data presentation, data verification (make conclusions). The results of the study found that the Covid-19 pandemic had a negative impact on the realization of Regional Original Income, and the Regional Income and Asset Financial Management Agency, especially the Regional Revenue Planning and Evaluation Sector, did not have a new strategy to increase local revenue. In fact, the Regional Government of South Nias Regency lowered its target of Original Regional Revenue in 2020 due to the unstable economy of the community.